The Controversy Of Sciences: Humanities Revisited - S. Sultan, Sabbar (Penerbit Universiti Sains Malaysia (USM Press), 2008)
The present paper is an attempt to explore the various views of the problematic relation between sciences and humanities. It is a relation marked by a great extent of discontent and misconception. It has six sections. The first section is a theoretical background. The second deals with Wells's fiction. The third is devoted to Huxley's. The fourth is about Snow's writings in this field. The fifth section discusses Albee's Who's Afraid of Virginia Woolf. The last section deals with the contribution of the post-modernistic writers to this controversy.